Review of Scott Cook, ed., Hiding the world in the world: Uneven discourses on the Zhuangzi - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2006)
The ten essays collected in this volume offer different perspectives on key issues in the Zhuangzi and should be warmly welcomed as a helpful addition to the field. The authors disagree on many things about the Zhuangzi; but there is certainly nothing "uneven" about the quality of their "discourses," which is uniformly high.